2013
DOI: 10.1007/s12105-013-0479-3
|View full text |Cite
|
Sign up to set email alerts
|

NUT Midline Carcinoma: A Case Report with a Novel Translocation and Review of the Literature

Abstract: NUT midline carcinoma (NMC) is a rare, genetically defined, highly lethal undifferentiated carcinoma occurring in the midline location of the neck, head or mediastinum. We present the case of a 23 year-old otherwise healthy Chinese male immigrant who presented with complaints of sore throat and right sided neck mass. The initial treatment was for likely EBV infection with streptococcal superinfection. Although continued investigation was pursued shortly after initial presentation, the mass had enlarged and bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Sections in which >20% of the cells showed split signals or 3 signals only were considered positive for NUT rearrangement. We reviewed previous reports [1][2][3][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25][26][27] published between 1991 and 2013 that described the details of immunohistochemical findings of NMC.…”
Section: Methodsmentioning
confidence: 99%
“…Sections in which >20% of the cells showed split signals or 3 signals only were considered positive for NUT rearrangement. We reviewed previous reports [1][2][3][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25][26][27] published between 1991 and 2013 that described the details of immunohistochemical findings of NMC.…”
Section: Methodsmentioning
confidence: 99%
“…In approximately 70% of cases, NUT (15q14) is fused to BRD4 (19p13.1), resulting in a BRD4-NUT fusion gene (3). In the remaining 30% of cases, NUT-variant tumors arise from fusion of the NUT gene to another partner gene such as BRD3, NSD3 (8p 11.23), or other uncharacterized genes (1,28).…”
Section: Genetics and Pathogenesismentioning
confidence: 99%
“…Its function remains equivocal (1,29). It has been suggested that the normal function of NUT is to increase histone acetylation by binding to and activating p300 histone acetyltransferase (28).…”
Section: Genetics and Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations